Impacts from Delaying Access to Retirement Benefits on Welfare Receipt and Expenditure: Evidence from a Natural Experiment - Umut Oguzoglu; Cain Polidano; Ha Vu (Institute for the Study of Labor (IZA), 2016)
Governments are responding to fiscal pressures associated with aging populations by increasing the eligibility age for publicly-funded retirement benefits. However, recent studies show large resulting increases in the receipt of alternative payments, which raises concern that welfare savings are offset by increased inflows into alternative payments. Using administrative data to examine the impacts of female eligibility age increases in Australia, we find little evidence of this. Instead, most of the increase in receipt is because the delay mechanically extends the receipt time of people already on alternative payments. The implication is that fiscal savings are not being jeopardized by opportunistic behaviour.
Keywords: H53; J26; J01; 330; welfare substitution; retirement; aging population